Survey of recent development in real-time biofeedback systems in sport - Hribernik, M.; Umek, A.; Kos, A. (Serbian Journal of Sports Sciences, 2020)
The recent advances in sensors and microprocessors have created the possibility of development of various types of biofeedback systems and applications. The ability of these systems to perform tasks in a relatively short time and with high accuracy enables also the development of real-time systems and applications. In this survey, we present the recent development and the current status of real-time biofeedback systems in sports from the beginning of 2019 and to the end of the first quarter of 2020. The survey focuses on the fully implemented real-time biofeedback systems, both simple and advanced. We include some other interesting studies that do not implement real-time biofeedback, but they present findings useful or crucial to future biofeedback systems. This survey includes 36 papers that study the use of real-time biofeedback in multiple sports. Almost one third of all included papers measure gait and running. This is an indicator that this field of science is still in its early stage of development. Other papers study sports like cycling, rowing and golf, etc. We also included some papers dealing with motion recognition and physical rehabilitation of athletes, as these two areas are an important part of more complex biofeedback systems and athlete recovery after injuries. This survey clearly shows that with the advancements in technology and sport science real-time biofeedback systems and applications will become not only beneficial but also indispensable for athletes and coaches.